Enzymatic maceration of bone: a gentler technique than boiling. (April 2015) - Uhre, Marie-Louise; Eriksen, Anne Marie; Simonsen, Kim Pilkjær; Rasmussen, Arne Redsted; Hjort, Benjamin Benn; Lynnerup, Niels
This proof of concept study investigates the removal of soft tissue from human ribs with the use of two common methods: boiling with a laundry detergent and using enzymes. Six individuals were autopsied, and one rib from each individual was removed for testing. Each rib was cut into pieces and afterwards macerated by one of the two methods. DNA extraction was performed to see the effect of the macerations on DNA preservation. Furthermore, the bone pieces were examined in a stereomicroscope to assess for any bone damage. The results demonstrated that both methods removed all flesh/soft tissue from the bones. The DNA analysis showed that DNA was preserved on all the pieces of bones which were examined. Finally, the investigation suggests that enzyme maceration could be gentler on the bones, as the edges appeared less frayed. The enzyme maceration was also a quicker method; it took three hours compared with the traditional method which took about 24 hours. However, a more standardised study should be performed to confirm this.